Math reading as an evolutionary process of thinking - Gallo Albarracín, Eliseo (Rastros Rostros, 2011)
This article presents the results of the research process “The mathematics reading process based on Piaget cognitive theory”,conducted by the research group Technologies of Information by the System Engineer program of the ucc, Bucaramanga satellite campus. A review is done on how the concepts and insights of the mathematical and sciences learning process are closely related to the process of evolution of knowledge that Piaget generalizes. Then a reflection on the evolutionary process of knowledge from the mathematical knowledge is presented, to finally reach a conclusion on the subject.